Inovasi Pelayanan Publik Melalui Aplikasi “Durenmas” Oleh Dinas Kependudukan & Pencatatan Sipil (Dindukcapil) Kabupaten Banjarnegara - Eva Agus Triana; Lina Aryani (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This research is motivated by the complexity of service problems at the Department of Population and Civil Registration (Dindukcapil) of Banjarnegara Regency during the 2016-2020 period. The purpose of this research is to analyze the usefulness of the application